Peran Perempuan dalam Hubungan Antar Gender: Tinjauan Filsafat Moral terhadap Otonomi Manusia - Maharani, Septiana Dwiputri (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
This research is an observation about female authonomy as a human being in determining her role in society. The assumption that emphase on women emansipation effort in history is always in change and development. In those days when polygamy was publicly practice, the main probelm is directed to equality of right in the context of women's role as wife and or mother, among the other wives. Nowadays, the probelm around the intergration of women's full-role as human resource in development activities. In global context, being influenced by world development, the women is inclained to equalize right and duty in the whole field of life, scarcely diffrentianting the natural reality. The autonomy is thought to be a motivation which the human activities decision base on.The research is an actual probelmatic research. The methods of philosophical analysis in the research are formulated as follows: interpretation, internal coherency, historical coherency, holistic, heuristic, and description.This research finds that the women do not yet use optimally their autonomy for they still under pressure in their decision making and it is not an act-decision that based on the individual consciousness.